Aerodynamics of Architecture and Building Complexes - Mahmood Razjouyan (صفه)
Today, the study of the speed of wind has become important in the design of urban regions due to their effect on human comfort, human behaviour and the reduction of air polution. In some countries, the analytical study of the speed and behaviour of wind in the areas undergoing constructional and reconstructional works, with regardes to the preconstructional operations, has become a necessity. In order to designate the speed and behaviour of wind in a contemporary urban texture, a general and positive theory is needed. Unfortunatly, this theory is not yet availabe. On the other hand, a great majority of experiments concluded within the wind tunnel are based upon this subject. Hence, on the basis of the results of such experiments, the presentation of guidelines for architects and urban designers becomes possible.